MEKANISME E-COMMERCE MELALUI BLOG DAN IMPLIKASINYA TERHADAP PENDAPATAN (STUDI KASUS PADA KOMUNITAS BLOGGER MALANG) - Firmansyah, Danny (Jurnal Ilmiah Mahasiswa FEB, 2012)
The rapid development of technology  today, allowing people  to  think creatively, to use technology to facilitate their lives, including their economic lives. One example is the development of technology used by many people today is the internet. The Internet allows people  to get a lot of useful information for  life, one media provider of information  on the internet  is a  blog.  In addition to being  a means of exchanging  information,  the blog was also a means  to earn an income  for the owner of the blog, by putting ads on the blog. This study aims  to provide an overview of how a blogger  to manage  their blog and how to earn money with a blog, ranging from choosing the theme of the blog to how bloggers  receive  revenue from ads  they  show  on the blog,  as well as the  various constraints faced  by  bloggers.  This study  took a  case study  in  Malang  blogger community.Keyword : Blog, Blogger, Internet, Income.